Analysis of Climate Change Induced Parameters of South-Eastern Coastal Islands of Bangladesh: Comparison from 1977 to 2017 - Prabal Barua; Syed Hafizur Rahman; Morshed Hossan Molla (Journal of Multidisciplinary Applied Natural Science, 2022)
Climate change is one of the biggest threats for the new millennium, and Bangladesh is considered as "Poster Child" as an impact on climate change in the world. The main focus of this study is to investigate the changing pattern of climate parameters, particularly temperature, rainfall, humidity, cloud coverage, and wind speed in two coastal islands of the southeastern coast of Bangladesh from 1977 to 2017. The linear regression model described that the temperature in Kutubdia and Sandwip islands was 0.0298 and 0.0444 times increased from 1977 to 2017. Besides, rainfall patterns in Kutubdia decreased by 0.4083, and Sandwip Islands increased by 0.875 every year from its previous counterpart. The humidity level also increased due to the rise of temperature and water availability for evaporation from irrigation. Moreover, significant changes in wind speed and the cloud coverage rate in the Island areas increased with the increasing value of temperature and humidity. It also means the rainfall rate increases with cloud cover in the sky. However, the study found decreasing rates of bright sunshine in the Island areas. The declining rate of sunshine is very high and is a matter of great concern for the agriculture and health sectors in particular areas. Therefore, the community's concept of climate parameters, association, and extremes is well apparent. Identify poor land use planning as the primary anthropogenic driver of the change, and they advocated boosting the capacity of linked fields that are in danger owing to climate change. To conclude, the coastal inhabitants recommended that taking preparedness would be easier if the information transmitted through quicker and reliable sources such as news broadcasts, phone messages, or the internet.